Remittances and Energy Consumption: A Panel Data Analysis for MENA Countries - Ari, Ayse (International Journal of Energy Economics and Policy, 2022)
In this paper, we investigate the effect of remittances on energy consumption. To this aim, we analyzed MENA countries over the 1977–2014 period. We used Westerlund and Edgerton’s (2007) cointegration test, the AMG estimator, and Dumitrescu and Hurlin’s (2012) panel causality tests. The results of the cointegration test showed there is a long-term relationship between remittance inflow and energy consumption. According to the AMG estimator, remittance inflow has a positive impact on energy consumption, indicating that increases in remittances will be followed by increases in energy consumption. The panel causality test displayed a bidirectional causal linkage between remittance and energy consumption. On the basis of these findings, we can say that authorities should take account of remittance inflow in their energy consumption and environmental degradation policies.